Penanaman Empati Digital di Era Social Society 5.0 - Latifa Fitriani; Abdullah Sahal Abu Nida; Slamet Slamet (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2022)
The social society 5.0 era increases the number of technology. There are some opportunities and challenges that remain. However, the lack of education when using technology can bring negative impacts. Therefore, the answer to solving this problem by digital literacy. Digital empathy is one of the strategies of digital literacy to foster the student’s character. This research aims to describe how to internalize digital empathy in social society 5.0. The type of this research used is a qualitative approach with study literature. The results showed that the way to foster digital empathy is by revitalizing education. Furthermore, revitalizing education is upgrading some points such as curriculum, media, method, teacher, and synergy among all school elements.